THE ROLE OF PEDAGOGICAL TECHNOLOGIES IN THE TEACHING OF HIGHER MATHEMATICS - Esanov Erkin Abdurahmonovich; Kuralov Bekjon Abdullayevich (Galaxy International Interdisciplinary Research Journal, 2022)
In this work, the mathematical competence of a future technical specialist is understood as the ability to use their mathematical knowledge in solving practical and theoretical problems that arise in their professional activities, expressing both fundamental mathematical knowledge and unified personal knowledge based on practical skills.